Topology optimization of multiphase materials with dynamic and static characteristics by BESO method. (January 2021) - Gan, Ning; Wang, Qianxuan
Highlights: An efficient method to solve the topology optimization of multiphase materials with static and dynamic characteristics. An improved multiphase material interpolation scheme is proposed to solve the local modal phenomenon in the dynamic frequency problem. The pre-processing density filtering scheme is introduced into the BESO method to eliminate the numerical instability problem. Abstract: The demand for advanced manufacturing is gradually turning to the multi-functional integrated structure, so the effective and innovative functional structure topology optimization design method can maximize the performance of the structure. This paper proposes a parallel topology optimization design method for dynamic and static characteristics of multiphase materials. The inherent discrete design variables of bidirectional evolutionary structure optimization (BESO) can clearly distinguish the topological boundaries of multiphase materials without the intermediate density materials. The pre-processing density filtering scheme is introduced into the BESO method to eliminate the numerical calculation instability problem. Then, the improved multiphase materials interpolation scheme can overcome the local modal phenomenon of vibration problems. Finally, a series of typical numerical examples show that the method is effective, efficient and easy to implement in multiphase materials topology optimization with dynamic and static characteristics.